Impacts of Hydrocolloids on Physical, Microbiological and Sensorial Qualities of Swai-Fish-Based Emulsions Subjected to High Pressure Processing - Jiranat Techarang (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. The objective of this study was to examine how konjac flour or carboxymethylcellulose (CMC) could improve the physical, microbiological, and sensorial qualities of pressurized Swai fish-based emulsions. The properties of the pressurized batches were also compared with those of the heated emulsions. Accordingly, Swai fish-based emulsions containing mixed fermented-soybeans were stabilized by either konjac flour or CMC, 0.1–0.3%. The fish batters were then subjected to pressurization (600 MPa/25°C/20 min) or thermal treatment (72°C/30 min). The results showed that both hydrocolloids enabled improvement of the color of fish emulsions. Regarding the impact of hydrocolloids on other properties, CMC addition enhanced water holding capacity, gel strength, and elasticity more than konjac flour addition. Regarding processing effects, pressurization gave rise to products with greater water holding capacity and higher sensorial scores than the thermal treatments. However, thermal treatments increased the gel strength and elasticity of the products more than pressurization. Overall, both processes could equally inhibit bacterial cells and some spores of B. subtilis.